(untitled) (Research, Society and Development, 2022)
To identify the opinion of the nursing team regarding the health team and family members involved in the management of delirium in the elderly. Exploratory, descriptive study with a qualitative approach, using semi-structured interviews conducted with 28 nursing professionals from a clinical unit in a tertiary-level hospital in the South Region. Data were categorized using the content analysis technique with the support of the NVivo ® software and discussed in the light of Paulo Freire’s thinking. Three thematic categories emerged: "Acting together with interdisciplinarity"; "The family context related to the care of the elderly with delirium" and "Structural limitation of the work process of the nursing team in managing delirium". There is a need for professionals from all areas involved in the care of the elderly with delirium to know the specific actions of each one in the control and prevention of the disorder, including the role of family members. This finding is in line with the thought of Paulo Freire, for whom the professional needs to progress from a naive awareness of their work and environment to have a critical awareness of their reality, recognizing their field of work and their actions, so that it is possible to transform your practice.